The Role of Parents, Teachers, and Self‑Esteem in Shaping Adolescents’ Premarital Sexual Behaviour - Sarah Astuti Hidayah; Risnawati Risnawati; Hestri Norhapifah; Dwi Hartati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Premarital sexual behaviour refers to intimate actions between two individuals who are emotionally attached but not legally married. Such behaviour is influenced by internal factors, including self‑esteem and depression, as well as external factors such as the roles of parents and teachers. Understanding these determinants is essential for developing effective adolescent reproductive‑health interventions. This study aimed to determine the relationship between parental roles, teacher roles, and self‑esteem with premarital sexual behaviour among adolescents at SMP Negeri 26 Samarinda. This research employed an observational analytic design with a cross‑sectional approach. The study involved 183 male and female students selected through stratified random sampling. Data were collected using structured questionnaires, and statistical analysis was performed using the chi‑square test to assess associations between variables. The findings showed no significant relationship between parental roles and premarital sexual behaviour among adolescents at SMP Negeri 26 Samarinda (p = 0.461). Similarly, no significant association was found between teacher roles and premarital sexual behaviour (p = 0.341). Self‑esteem was also not significantly associated with premarital sexual behaviour (p = 0.913). The study concludes that parental roles, teacher roles, and self‑esteem are not significantly associated with premarital sexual behaviour among adolescents at SMP Negeri 26 Samarinda. These results suggest that other factors may play a more substantial role in influencing adolescent premarital sexual behaviour and should be explored in future research.Keywords: parents; teachers; self‑esteem; premarital sexual behaviour